Guidelines for implementing and evaluating the Portuguese drug strategy - Beusekom, I. van (Ineke); Loo, Mirjam van het.; Kahan, James P.; RAND Europe; Rand Corporation; Luso-American Development Foundation (Santa Monica, CA : RAND, 2002)
Portugal recently changed its drug policy by adopting a strategy based upon a series of principles to contain and reduce the negative effects of substance abuse. The flagship of this strategy is the decriminalization of consumption of all types of drugs and possession of these drugs for personal use. The strategy has begun to be implemented through a series of laws and administrative decisions, of which the decriminalization law took effect on 1 July 2001. Other laws address harm reduction, risk reduction, prevention, treatment and rehabilitation. This report analyzes the new Portuguese Drug Strategy and develops recommendations for its implementation and evaluation. To do this, it examines the history of Portuguese society and its drug problem over the past 75 years, looks in detail at the strategy, proposed laws and action plans, and examines them in light of the existing literature on drugs and drug abuse. The main question addressed in this project was: Which parts of the National Drug Strategy deserve priority in its implementation and how should the effects of implementation of the Strategy be evaluated? This was divided into three subquestions: (1) What are the objectives of the National Drug Strategy? (2) What are the most appropriate ways of prioritizing the individual components of the National Drug Strategy? and (3) How can the real effects of the National Drug Strategy be assessed?
"February 2002."
"RAND Europe."
Includes bibliographical references (p. 57-58).
Also available on the internet via WWW in PDF format.
Keywords: Drug abuse -- Government policy -- Portugal -- Evaluation; Drug legalization -- Portugal; Narcotics, Control of -- Portugal -- Evaluation